Black Cumin Seed Oil Antidiabetogenic by Increasing Pancreatic P53 Expression - Akrom Akrom; Rizma Nurfadjrin; Endang Darmawan; Titiek Hidayati (Intelektual Pustaka Media Utama, 2018)
Black cumin seed oil (BCSO) contains many thymoquinone and unsaturated fatty acids that act as antioxidants. Thymoquinone was thought to inhibit pancreatic damage and prevent hyperglycemia by involving p53. The study aimed to determine the BCSO effect on Malondialdehyde (MDA) levels and p53 expression of pancreatic tissues in alloxan-induced Sprague Dawley (SD) rats. This study used Pre and Post Test with Control Group Design with 49 male Sprague Dawley rats aged 30 days weighing 150 - 300 gram. Rats were divided into 7 groups: Group I, the normal control group receiving standard feeding and drinking; Group II, the negative control group receiving alloxan; Group III & IV, the treatment groups, receiving BCSO with a dose of 6.9 mg/KgBW (BCSO6.8) and 68 mg/KgBW (BCSO68 group); Group V, the positive control 1 group receiving simvastatin 10 mg/KgBW; Group VI, the positive control 2 group receiving vitamin C 18 mg/200mgBW; Group VII, the solvent control receiving DMSO. The treatment groups received two different doses per day for 9 days orally. Blood MDA and glucose levels were determined by spectrophotometry and p53 expression of pancreas tissues were read by a pathologist. The results show that the BCSO68 group had a decreased activity of MDA and glucose but a higher expression of p53 in pancreatic tissues compared to the BCSO6.8 group. Decreased Malondialdehyde levels in the BCSO68 group were similar to those in the vitamin C group but lower than those in the simvastatin group (p<0.05). It can be concluded that the BCSO administration of 68 mg/KgBW per day can decrease blood Malondialdehyde and glucose levels and increase p53 expression.